PELATIHAN MEMBANGUN KOMUNITAS LITERASI BERBASIS MASYARAKAT MENUJU DESA TANGGUH DAN BERKELANJUTAN DI KECAMATAN WONOSARI KABUPATEN MALANG - Ali Maksum; Ayu Kartika; Mas'ud Effendi; Komang Chandra Brata; Abdul Rachman Sopyan (Wisesa: Jurnal Pengabdian Masyarakat, 2024)
The need for a literacy community forum by village communities in order to create a sustainable and resilient village is increasingly urgent. Therefore, recognition of the literacy movement of village communities is needed by utilizing existing social capital and social resources. Increasing public literacy is an effort to solve problems in the digital era which have an impact on the socio-economic side. Through this activity, it is hoped that community-based literacy communities will emerge and be initiated to develop village potential, which will ultimately have an impact on the resilience and welfare of community members. This activity was using the participatory action research method with direct involvement between the team and the target community. This activity has raised awareness among participants who are stakeholders in each Wonosari District Village regarding the importance of literacy as the key to solutions to village problems. Cognitively, participants already have knowledge of the steps to initiate a literacy community in each village, the ability to use the internet to search for accurate and credible sources of information, as well as the ability to utilize the internet and social media for the benefit of tourism and community entrepreneurship, and a channel for community voices.